Fatores determinantes da prevalência e diversidade de hemosporídeos em aves silvestres no nordeste brasileiro: um estudo temporal - Raquel Andrade Rodrigues (2019)
The host-parasite relationship is a complex interaction in wich parasites can influence host populations and communities, but, on the other hand factors related to the host may also influence the prevalence and infectivity of the parasites. A good model for the study of parasite-host interaction dynamics and the role of parasites in the evolution of the life history of their hosts are avian haemosporidian - parasites with high diversity that infect a wide range of birds worldwide. Therefore, the present study explored the factors that influence the parasite-host interaction in natural environment, exploring (i) how ecological factors and birds’ life-history traits may influence parasites’ infection probability and prevalence, and (ii) how parasites can affect behavior and survival of their hosts. The birds were captured over 24 months using mist-nets in a tropical coastal vegetation region, named Restinga - a type of vegetation of the Atlantic Forest biome – located in Barreira do Inferno Rocket Launch Center (CLBI) of the Brazilian Air Force, in Parnamirim, State of Rio Grande do Norte. Initially, we tested whether the prevalence of Plasmodium and Haemoproteus is related to individual characteristics and species-specific traits of the hosts, and environmental factors of the study area. We detected a prevalence of 22.3% and 27 haemosporidian lineages infecting the 1,443 birds captured. Plasmodium prevalence was positively influenced by temperature, which may be related to its influence on vectors (Diptera: Culicidae) abundance in the study area. Migratory birds were less likely to be infected by Haemoproteus, but not by Plasmodium, which may indicate that Haemoproteus lineages detected should display higher specificity to CLBI resident birds. Among the Haemoproteus infections detected, there was a strong interaction between the white-lined tanager (Tachyphonus rufus) and the lineage H. (Parahaemoproteus) TARUF02, which led us to explore which factors influence the survival and capture of white-lined tanager, and the prevalence and probability of infection of this host by Haemoproteus. The survival probability was ~10% lower in infected birds that were breeding when compared to uninfected and non-breeding birds. This result indicates that even birds chronically infected by Haemoproteus may suffer substantial impacts on their survival and fitness. Birds were 14% more likely to be caught by mist-nets when infected, suggesting a change in behavior of infected birds that make them more susceptible to capture by nets. The avian haemosporidian community in CLBI adds new information on the distribution and richness of avian haemosporidian, depicting the ecological factors and host traits that influence the dynamics of infection in the natural environment, and demonstrates the complex and variable nature of this host-parasite system.